A Computationally Designed Prefusion Stabilized Human Metapneumovirus Fusion Protein Vaccine Antigen Elicited a Potent Neutralization Response - Michael Kishko; Antonia Stuebler; Sukanya Sasmal; Yvonne Chan; Dean Huang; Christopher Reyes; Jasmine Lin; Owen Price; Ana Kume; Katie Zong; Christine Bricault; Judith Alamares-Sapuay; et al. (Vaccines)
Background/Objectives: Human metapneumovirus (hMPV) is a leading cause of respiratory infections in the elderly, with high morbidity and mortality and with no vaccines or specific therapies available. The primary protective antigen of hMPV is the fusion protein, and its prefusion conformation (pre-F) is considered the most promising target for vaccine development. Methods: Utilizing computational design strategies focused on intraprotomer interface stabilization, we designed hMPV pre-F recombinant subunit vaccine candidates based on the most prevalent A2 subtype and characterized them in vitro and in vivo, benchmarking to the prototypical hMPV pre-F stabilized by an introduction of a proline at site 185. Results: The top candidate (N46V_T160F) yielded 14.4 mg/L with a melting temperature of 79.3 °C as compared to 5.7 mg/L and 70.4 °C for the benchmark. By employing monoclonal antibody binding to all six antigenic sites of hMPV pre-F, we confirmed this construct retained all pre-F specific antigenic sites and that the key sites Ø and V were stable at 4 °C for up to 6 months. When immunogenicity of N46V_T160F was evaluated in mice, it induced higher binding and neutralizing antibody titers than the benchmark, which stemmed in part from increased levels of site Ø and site II targeting Abs. Further, this A2 based construct induced cross-neutralizing Abs against all four hMPV subtypes. Lastly, our construct exhibited similar immunogenicity as the recently published next-generation hMPV pre-F constructs, DS-CavEs2 and v3B_Δ12_D454C-V458C. Conclusions: N46V_T160F is a promising hMPV vaccine candidate paving the way for further development and optimization.